Methods of flexibility training (IAAF @-Letter for CECS Level II Coaches, 2004)
During the last two decades, informed coaches` attitudes have changed, first with relation to the value of flexibility and second with regard to the way it should be done. Today, flexibility training is an essential component of any training program. The oldfashioned approach was to stretch to the point of pain and with inadequate build-up. It is important for coaches to understand that stretching cannot be rushed and that it takes several years of flexibility training for an athlete to become proficient in carrying out these exercises (Bloomfield & Wilson, 1998, p. 266). To obtain muscle benefits from a training program to enhance range of movement (ROM), participants must know the capabilities and limitations of the program and how to differentiate between various types of programs (Alter, 2004, p. 5). Definition of a flexibilitytraining program A flexibility-training program is defined as a planned, deliberate, and regular program of exercises that can permanently and progressively increase the usable ROM of a joint or set of joints over a period of time (Alter, 2004, p. 5). Often the term flexibility exercise is used synonymously with stretching exercise (Pezzullo & Irrgang, 2001, p. 113). However, Kisner and Colby (2002) emphasize that "stretching and ROM exercises are not synonymous terms. Stretching takes soft tissue structures beyond their available length to increase ROM. ROM exercises stay within the limits of tissue extensibility to maintain the available length of tissues." (p. 18).